Knowledge and Awareness of Alternative and Complementary Medicine among Oncology Patients: An In-depth Analysis. - KARABULUT GÜL, Şule; ÇOLAKOĞLU, Melek; TUNA, Sinem; ŞEKER, Enes; ÖZKAN, Özge; ALOMARI, Omar; YÜKSEL, İrem; TEPETAM, Hüseyin; GÜL, Hakan Levent (Turkish Journal of Oncology / Türk Onkoloji Dergisi, 2023)
OBJECTIVE This study investigates the increasing use of complementary and alternative medicine (CAM) among oncology patients, surpassing conventional medical treatments. Factors driving this trend go beyond medical intervention. The study aims to shed light on patients' awareness and knowledge of CAM practices during and after treatment. METHODS 161 cancer patients voluntarily participated, providing demographic information, gender, age, marital status, and cancer type. Data on CAM use and knowledge were collected and analyzed using the Statistical Package for the Social Sciences 22.0 program. P<0.05 was considered statistically significant, with approval from the ethics committee. RESULTS 53.4% were over 60 years old, and 57.8% were women. 86.3% were familiar with at least one CAM method, and 29.2% actively used CAM. Women used CAM significantly more than men. Usage was higher in individuals under 60 years and single patient. CAM was more popular among breast cancer patients. Black cumin and turmeric were the most frequently used herbal methods. Patients mainly acquired CAM knowledge from friends and online sources. CONCLUSION The study revealed a lower CAM usage rate compared to similar international studies in different settings, likely due to the focus on patients seeking treatment at the radiation oncology department. As physicians, it is crucial to expand our knowledge and educate oncology patients about CAM applications. Bridging the information gap will cater to the growing interest in CAM among patients and ensure informed decisions regarding treatment options.